A Projection Analysis of News Critical Literacy Among Chinese EFL Learners: An SFL Approach - Zaibing Luo; Pan Xie (SAGE Open)
Critical literacy in EFL context has been examined from different perspectives. However, there is limited empirical evidence of how news critical literacy is examined discursively among college EFL learners. By deploying a Projection profile from Systemic Functional Linguistics, this paper contributes to the written evaluation of college EFL learners’ news critical literacy. The data consisted of 236 news critiques from two cohorts of Chinese EFL learners. The results show that college EFL learners in China are more subjected to the projection of locution and subjective-implicit projection in news critiques, presenting similar choices about projection grammar but reverse orientations in news criticizing context. Moreover, Chinese EFL learners are adept in projecting function for iconic sequencing of information, text sharpening, message retrospecting, and co-textual reasoning, manifesting a critical awareness in functional literacy of news discourse. Various projections also place Chinese EFL learners into a cline of discursive identities among projectors, speakers and discoursal community members, which indicates that Chinese EFL learners are disengaged in discerning news information and passive on news values and social context. The findings implicate that a projection-based trinocular lens is a discursively effective approach for delimiting Chinese EFL learners’ news critical literacy while corroborating that discursive technology, contextual orientation and critical awareness are crucial elements in news critical literacy. Pedagogical implications for news literacy education and media communication toward EFL learners are also discussed.